Taiwanese deep-water chitons (Mollusca: Polyplacophora) and survey of chiton fauna of Taiwan - Sirenko, Boris (Zootaxa, 2018)
Sixteen deep-sea polyplacophoran species are reported in this article, fifteen of which were found for the first time in the waters of Taiwan. Two of these species, Leptochiton taiwanensis n. sp. and L. wui n. sp., are described as new to science. Several of these species are distributed near Japan and in other areas of the western Pacific Ocean. Eight of the reported species live and feed on sunken wood. A survey of the polyplacophorans of Taiwan has also been conducted. The updated list of chitons collected near Taiwan at all depths contains 34 species. Seventeen of these species are shallow-water and seventeen species are deep-water chitons.